Sociopolitical activist brands. Issue 1 (1st April 2021) - Schmidt, Holger Joerg; Ind, Nicholas; Guzmán, Francisco; Kennedy, Eric
Abstract : Purpose: This paper aims to shed light on the emerging position of companies taking stances on sociopolitical issues and the impact this has on consumers. Design/methodology/approach: The paper uses focus groups, interviews and consumer experiments in various countries, to provide insights as to why brands are taking sociopolitical stances. Findings: Consumers expect brands to take a stance on sociopolitical issues. However, to be credible, a stance needs to be rooted in a long-term commitment that aligns with the brand's strategy and values. Perceived authenticity is key. Research limitations/implications: Future studies should aim at broader generalizability and should address various industries. Practical implications: Differentiating a brand through a sociopolitical stance requires a strategic approach. Brand managers need to identify which issues they should support, how to engage with them and the risks and opportunities involved. Originality/value: While the impact of brands adopting a sociopolitical stance has been discussed in the mainstream media, there has been a lack of empirical evidence to support the arguments. The results of the four studies discussed in the paper provide insights and demonstrate the brand-related opportunities and risks of taking a sociopolitical stance.